Analisis Hukum Perbankan Konversi Bank Konvensional Menjadi Bank Syariah - nurhadi nurhadi (Rumah Jurnal Sekolah Tinggi Agama Islam An-Nawawi Purworejo, 2021)
Conventional Banks can change business activities into Sharia Banks, but not vice versa. Changes in business activities for commercial banks and rural banks must obtain permits and meet requirements. After permission is obtained, it must clearly state the word